High incidence of acute and subacute ischaemic foci on brain MRI in patients with a diagnosis of acute pulmonary embolism and confirmed patent foramen ovale - Nykl, Radomír; Hutyra, Martin; Čecháková, Eva; Přeček, Jan; Vindiš, David; Richter, David; Táborský, Miloš (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND: Pulmonary embolism (PE) is a common and potentially life-threatening diagnosis when a certain amount of thrombotic mass obstructs blood flow through the pulmonary circulation. The finding of acute and subacute ischaemic foci on magnetic resonance imaging (MRI) of the brain in a group of patients with this diagnosis in whom we demonstrate the presence of patent foramen ovale (PFO) by transoesophageal echocardiography (TEE) is surprisingly high. METHODS: A total of 129 patients with a diagnosis of pulmonary embolism (confirmed by computed tomography with contrast agent, CTA) who consented to further examination were examined by transthoracic echocardiography (TTE) and transoesophageal echocardiography (TEE) with contrast agent, underwent magnetic resonance imaging of the brain according to a specific protocol, and underwent a comprehensive baseline laboratory examination. RESULTS: In our group of 129 patients, we found the presence of PFO in 36.4% (n=47) of them. A total of 5.4% (n=7) patients had asymptomatic acute and subacute ischaemic changes on brain MRI; 6 of them had concomitant PFO. The statistically significant correlation between troponin levels and the presence of pathological findings on MRI and the trend of a similar correlation for NT-proBNP values is also very interesting finding. CONCLUSIONS: The association between the presence of PFO and the occurrence of symptomatic or asymptomatic findings on brain MRI is a well-known fact (the issue of paradoxical embolism) but the high frequency of acute and subacute lesions on brain MRI in the group of patients with a diagnosis of acute PE is surprising.
Keywords: echokardiografie; dospělí; Magnetic Resonance Imaging; Female; Acute Disease; Adult; ženské pohlaví; lidé; magnetická rezonanční tomografie; Echocardiography; ischemie mozku; Pulmonary Embolism; Incidence; plicní embolie; Male; incidence; Aged; Brain Ischemia; Echocardiography, Transesophageal; echokardiografie transezofageální; akutní nemoc; foramen ovale apertum; lidé středního věku; Foramen Ovale, Patent; senioři; mužské pohlaví; Middle Aged; Humans